Keeping the best of two worlds: Linking CGE and microsimulation models for policy analysis - Konstantins Beņkovskis; Ludmila Fadejeva; Anna Pluta; Anna Zasova (University of Essex, Institute for Social and Economic Research (ISER), 2023)
In this paper, we link a CGE model with the tax-benefit microsimulation model EUROMOD for Latvia. The model linkage is done using an iterative top-down bottomup approach, ensuring the convergence of changes in disposable income, employment and wage in both models. We also incorporate the unreported wage payments in CGE and EUROMOD to account for the substantial labour tax non-compliance in Latvia and improve the modelling of the fiscal sector. Several simulations demonstrate the advantages of the joint CGE-EUROMOD system over the individual macro and microsimulation models. The lack of income distribution aspect and the scarcity of fiscal instruments in CGE can be overcome by the features of EUROMOD. The CGE model, on the other hand, provides macroeconomic spillovers that are missing in the simulations of EUROMOD.
Keywords: C68; D58; D90; J46; 330; EUROMOD; CGE model; model linkage; informal sector